2005
DOI: 10.1200/jco.2005.05.187
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Teratoid/Rhabdoid Tumors (ATRT): Improved Survival in Children 3 Years of Age and Older With Radiation Therapy and High-Dose Alkylator-Based Chemotherapy

Abstract: Children presenting with ATRT before the age of 3 years have a dismal prognosis. ATRT presenting in older patients can be cured using a combination of radiation and high-dose alkylating therapy. Older patients with relapsed ATRT can have salvage treatment using ICE chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
301
3
24

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 378 publications
(349 citation statements)
references
References 27 publications
21
301
3
24
Order By: Relevance
“…This occurred in the context of 2 retrospective studies that demonstrated an association between adjuvant RT and improved OS. 10,12 We confirmed this modest association between increased survival and RT in a rigorous statistical manner with the use of a landmark analysis to account for immortal time bias, which potentially can limit studies that use observational data. RT was a positive prognostic factor for survival in univariate analysis and remained significant in multivariate models, further supporting a robust association between RT and improved OS in ATRT.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…This occurred in the context of 2 retrospective studies that demonstrated an association between adjuvant RT and improved OS. 10,12 We confirmed this modest association between increased survival and RT in a rigorous statistical manner with the use of a landmark analysis to account for immortal time bias, which potentially can limit studies that use observational data. RT was a positive prognostic factor for survival in univariate analysis and remained significant in multivariate models, further supporting a robust association between RT and improved OS in ATRT.…”
Section: Discussionmentioning
confidence: 52%
“…The benefits of greater tumor resection have not been consistent in other studies, suggesting that resection alone is not sufficient for long-term survivorship in patients with ATRT and establishing the need for adequate adjuvant therapy. 9,10,12,14 Data describing chemotherapeutic regimens were not available for analysis; however, chemotherapy often is administered in the initial postoperative period to patients with ATRT. Because most children aged 3 years receive chemotherapy as a way of postponing RT, chemotherapeutic strategies for ATRT have been among the best studied issues in ATRT management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations